The nature of information, and the effective use of information in rural development - Hester W.J. Meyer (Information Research: An International Electronic Journal)
Introduction. We report on the role of information in the development of rural communities where the impact of the oral tradition remains very strong. The nature of the attributes, and the particular type of communication mechanisms to be used, have been proposed as key factors in the use of information in rural communities. Method. Literature studies have been conducted to determine the nature of information, and information handling skills of traditional people. An in-depth study with field visits provided information on real-life practices. Analysis. A qualitative analysis has been carried out to match evidence from a case study and field visits with evidence in the literature. Requirements for the development process were taken into account. Results. A comparison of the attributes of information with the requirements for development of traditional people revealed that certain attributes of information are conducive to development while others can be counterproductive to the development process if not addressed properly. Conclusion. > The successful use of information as a resource for development depends in large part on knowledge of the nature of information and the ability of senders to apply appropriate communication mechanisms understandable to traditional people. This has implications for people involved in the development of rural communities.